Development of multiple-frequency wireless coordinative motor drives - Jiang, Chaoqiang (2019)
This paper proposes and implements a novel class of inductor-capacitor-capacitor wireless coordinative DC motor drives, which not only performs selective wireless power to motors, but also achieves power equalization to ensure the same operation for isolated robotic arms. The key is to make use of the selective wireless power transfer with several resonant frequencies and then use only one transmitter with the inductor-capacitor-capacitor compensation network to provide multiple-frequency transmission without relying on the switched-capacitor array. In order to provide simultaneous and independent wireless power to different motors and hence achieve the desired coordinative motion, a time-division multiplexing scheme and burst firing control are newly employed. Thus, the wireless power transfer system with multiple receivers can achieve better flexibility and simplicity. Both finite element analysis and experimental results are given to verify the validity of the proposed inductor-capacitor-capacitor wireless coordinative DC motor drive. As a result, the motors can achieve independent motion with 1200 rpm and simultaneous motion with 400 rpm when the torque is 10 Ncm, and the operating frequencies are set at 110 kHz and 130 kHz.